Penerapan Hipnosis Lima (5) Jari Terhadap Tingkat Kecemasan Pada Mahasiswa Tingkat Akhir Di Universitas ’Aisyiyah Surakarta - Nur Aini Setiawan; Ida Nur Imamah (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Background : Final year students are required to write scientific papers (theses), namely about topics in particular fields. The final Project is a mandatory requirement that students must run, during the process of preparing the final project students experience tension and anxiety faced in compiling the final project. Action to overcome anxiety is with pharmacological and non-pharmacological therapies. Five-finger hypnosis is one of the non-pharmacological therapies in the form of Self-hypnosis that can cause a relaxing effect, thereby reducing tension and anxiety. Objective : Knowing the effected of five (5) finger hypnosis on anxiety levels in final-year students at 'Aisyiyah University Surakarta. Method : Using case studies. This type of research uses a pretest-post-test design. A sample of 2 students who are compiling their final project experienced moderate to severe of anxiety levels. Measurement of anxiety levels using the HARS questionnaire. Results : The level of anxiety before being given five (5) finger hypnosis was severe and moderate anxiety and after being given five (5) finger hypnosis the anxiety level dropped to moderate and mild anxiety. Conclusion: There was a significant influence on the anxiety experienced by students of 'Aisyiyah University Surakarta before and after being given five (5) finger hypnosis therapy.